Efektivitas Hukum Humaniter Internasional Dalam Melindungi Cagar Budaya Di Negara Konflik - Astuti, Mirsa (Universitas Muhammadiyah Sumatera Utara, 2018)
War is an instinct for self-defense that applies both in association between humans and relationships between nations. Therefore the history of war is as old as the history of mankind. In armed conflict there are a lot of cultural objects which are destroyed by bombs or bullets used to attack enemy targets by parties in conflict. Although protection of cultural heritage objects has been regulated in an International Convention, there are still behaviors that cause damage to even the destruction of cultural objects. The procedure for collecting data is in the form of documentation of notes or quotes, search of legal literature, books and others related to the identification of problems both offline and online which are then analyzed through the content analysis method (centent analysis method) with a focus on the issue of how effective the law is international humanitarian in protecting cultural heritage in conflict countries. The results of the study it is known that cultural objects are the cultural identity of the community, so that attacks on them often increase conflict escalation. Air and remote bombing attacks increase damage to cultural objects resulting from armed conflict.